Pengaruh Disiplin dan Kemandirian Belajar terhadap Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar - Nurriskah, Yuniatun Dwi; Joharman, Joharman; Hidayah, Ratna (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to prove the positive effect of: (1) learning discipline on mathematics learning outcomes; (2) independence in learning on mathematics learning outcomes; (3) discipline and independence in learning on mathematics learning outcomes. The study used correlational method. Data analysis used simple regression analysis and multiple regression analysis with a significance level of 5%. The results showed that: first, there was positive effect between learning discipline and mathematics learning outcomes (tcount = 4.647> ttable = 1.652 and Sig. 0.000 <0.05). The coefficient of determination was 9%. The regression equation was Y = 1.621 + 0.054X1. Second, there was positive effect between independence in learning and mathematics learning outcomes (tcount = 6.941> ttable = 1.652 and Sig. 0.000 <0.05). The coefficient of determination was 18.1%. The regression equation was Y = -8,167 + 0.084X2. Third, there was positive effect between discipline and independence in learning on mathematics learning outcomes (Fcount = 24,559> Ftable = 19,491 and Sig. 0,000 <0.05). The coefficient of determination was 18.5%. The regression equation was Y = -9,367 + 0.013X1 + 0.075X2. It concludes that there is positive effect between discipline and independence in learning on mathematics learning outcomes of fifth grade students of public elementary schools in Klirong sub-district in academic year of 2019/2020 simultaneously or separately.